Evropska diplomatija i obuzdavanje srpskog nacionalizma / European Diplomacy and Restraint on Serbian Nationalism: Novo balkansko "mesečarenje" / New Balkan "Moonlighting" - Todorović, Zoran (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The paper points to the lack of re-examination of the consequences of the long-lasting and continuous nationalist actions of Serbia aimed at expanding and homogenizing the ethnic state, which is still plaguing international relations in the Balkans and Europe today. The long-lasting nationalist paradigm most brutally manifested in the wars of the 1990s continues to operate through tried and tested patterns of subversiveness, incitement propaganda, and irredentism in the areas that Serbia still counts as its political space today. The paper raises the question and seeks to answer whether European diplomacy has the power to curb the political-territorial pretensions of Serbia that it has traditionally manifested towards Bosnia and Herzegovina, Montenegro, Northern Macedonia and Croatia. Then, is it certain that the European Union is finally transforming the Serbian nationalist state into a civilian democratic state, or will European leaders "moonlight" over the Balkans while Russian hegemonism uses Greater Serbian nationalism to destabilize Europe. How certain it is to succeed in doing so without the assistance of the United States of America, or will it be established that, to put it bluntly, only the US embassies in the Western Balkans have the power to show Balkan nationalist leaders how irrelevant they can be if peace is threatened again.